Nomenclatural Studies Toward a World List of Diptera Genus-Group Names. Part IV: Charles Henry Tyler Townsend - Evenhuis, Neal L.; Pont, Adrian C.; Whitmore, Daniel (Zootaxa, 2015)
The Diptera genus-group names of Charles Henry Tyler Townsend are reviewed and annotated. A total of 1506 available genus-group names in 12 families of Diptera are listed alphabetically for each name, giving author, year and page of original publication, originally included species, type species and method of fixation, current status of the name, family placement, and a list of any emendations of it that have been found in the literature. Remarks are given to clarify nomenclatural and/or taxonomic information. In addition, an index to all the species-group names of Diptera proposed by Townsend (1595, of which 1574 are available names) is given with bibliographic reference (year and page) to each original citation. An appendix with a full bibliography of almost 650 papers written by Townsend is presented with accurate dates of publication. Two new replacement names are proposed for preoccupied genus-group names and both are named to honor our good friend and colleague, James E. O’Hara, for his decades of work on tachinids: Oharamyia Evenhuis, Pont & Whitmore, n. name, for Lindigia Townsend, 1931 [Tachinidae] (preoccupied by Karsten, 1858); Jimimyia Evenhuis, Pont & Whitmore, n. name, for Siphonopsis Townsend, 1916 [Tachinidae] (preoccupied by Agassiz, 1846). Earlier dates of availability are found for the following: Eucnephalia Townsend, 1892 [Tachinidae]; Gabanimyia Townsend, 1914 [Tachinidae]; Incamyia Townsend, 1912 [Tachinidae]; Muscopteryx Townsend, 1892 [Tachinidae]; Philippolophosia Townsend, 1927 [Tachinidae]; Pseudokea Townsend, 1927 [Tachinidae]. Corrected or clarified included species and/or corrected or clarified type-species and methods of typification are given for: Alitophasia Townsend, 1934 [Tachinidae]; Almugmyia Townsend, 1911 [Tachinidae]; Arachnidomyia Townsend, 1934 [Sarcophagidae]; Austenina Townsend, 1921 [Glossinidae]; Austrohartigia Townsend, 1937 [Sarcophagidae]; Awatia Townsend, 1921 [Muscidae]; Azygobothria Townsend, 1911 [Tachinidae]; Brachymasicera Townsend, 1911 [Tachinidae]; Calocarcelia Townsend, 1927 [Tachinidae]; Cnephalodes Townsend, 1911 [Tachinidae]; Cyacyrtoneura Townsend, 1931 [Muscidae]; Cyrtoneuropsis Townsend, 1931 [Muscidae]; Cyrtosoma Brauer & Bergenstamm, 1893 [Tachinidae]; Epiphyllophila Townsend, 1927 [Tachinidae]; Eucalodexia Townsend, 1892 [Tachinidae]; Eumesembrina Townsend, 1908 [Muscidae]; Eumyobia Townsend, 1911 [Tachinidae]; Eusisyropa Townsend, 1908 [Tachinidae]; Gabanimyia Townsend, 1914 [Tachinidae]; Galactomyia Townsend, 1908 [Tachinidae]; Girschneria Townsend, 1919 [Tachinidae]; Gymnochaetopsis Townsend, 1914 [Tachinidae]; Himantostomopsis Townsend, 1921 [Tachinidae]; Incamyia Townsend, 1912 [Tachinidae]; Lithoexorista Townsend, 1921 [Tachinidae]; Muscopteryx Townsend, 1892 [Tachinidae]; Myocuphocera Townsend, 1931 [Tachinidae]; Myxexoristops Townsend, 1911 [Tachinidae]; Neojurinia Townsend, 1914 [Tachinidae]; Newsteadina Townsend, 1921 [Glossinidae]; Ommasicera Townsend, 1911 [Tachinidae]; Ophirion Townsend, 1911 [Tachinidae]; Ophiriodexia Townsend, 1911 [Tachinidae]; Ophiriosturmia Townsend, 1911 [Tachinidae]; Opsozelia Townsend, 1919 [Tachinidae]; Paleotachina Townsend, 1921 [Tachinidae]; Palexorista Townsend, 1921 [Tachinidae]; Phasiatacta Townsend, 1911 [Tachinidae]; Philippolophosia Townsend, 1927 [Tachinidae]; Phrissopolia Townsend, 1908 [Tachinidae]; Pseudokea Townsend, 1927 [Tachinidae]; Pygocalcager Townsend, 1935 [Tachinidae]; Trichobius Townsend, 1891 [Hippoboscidae]; Villeneuvia Townsend, 1921 [Tachinidae]; Zonoepalpus Townsend, 1927 [Tachinidae]; Zygosturmia Townsend, 1911 [Tachinidae]. The following names previously treated as available are shown to be unavailable.—Genera: Denatella Townsend, 1931, n. stat. [Calliphoridae]; Epseudocyptera Townsend, 1927, n. stat. [Tachinidae]; Eustomatodexia Townsend, 1892, n. stat. [Tachinidae].—Species: Epseudocyptera epalpata Townsend, 1927, n. stat. [Tachinidae]; Eustomatodexia insulensis Townsend, 1892, n. stat. [Tachinidae]. The following genus-group names, not listed in previous regional catalogs, are treated here: Arabisca Townsend, 1935 [Sarcophagidae]; Eupeleteria Townsend, 1908 [Tachinidae]; Macropatelloa Townsend, 1931 [Tachinidae]; Neohypostena Townsend, 1915 [Tachinidae]; Neometapodia Townsend, 1892 [Sarcophagidae]; Tricyclopsis Townsend, 1916 [Calliphoridae]; Trongia Townsend, 1916 [Calliphoridae]. Previous First Reviser actions for multiple original spellings that were overlooked by other workers are given for the following: Genus-group names—Microchaetona Townsend, 1919 [Tachinidae]; Neopodomyia Townsend, 1927 [Tachinidae]; Opsophytopsis Townsend, 1918 [Sarcophagidae]; Prohypotachina Townsend, 1933 [Tachinidae]; Rhinomyodes Townsend, 1933 [Tachinidae]; Servilliodes Townsend, 1926 [Tachinidae]; Tephromyiella Townsend, 1918 [Sarcophagidae]; Thelairochaetona Townsend, 1919 [Tachinidae]; Xanthopteromyia Townsend, 1926 [Tachinidae]. Species-group names—Brachybelvosia brasiliensis Townsend, 1927 [Tachinidae]; Neocraspedothrix nova Townsend, 1927 [Tachinidae]. The following nominal genera enter into new synonymies: Bathytheresia Townsend, 1915 under Billaea Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Brachycoma Brauer & Bergenstamm, 1889 under Brachicoma Rondani, 1856, n. syn. [Sarcophagidae]; Chaetolyga Brauer, 1880 under Carcelia Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Chaetoprosopa Marschall, 1873 under Choeteprosopa Macquart, 1851, n. syn. [Tachinidae]; Chlororhynchomyia Senior-White, Aubertin & Smart, 1940 under Metallea Wulp, 1880, n. syn. [Rhiniidae]; Chrysomyia Macquart, 1835 under Chrysomya Robineau-Desvoidy, 1830, n. syn. [Calliphoridae]; Echinomyia Fischer von Waldheim, 1808 under Echinomya Latreille, 1805, n. syn. [Tachinidae]; Euhypochaetopsis Townsend, 1928 under Campylocheta Rondani, 1859, n. syn. [Tachinidae]; Graphomyia Macquart, 1834 under Graphomya Robineau-Desvoidy, 1830, n. syn. [Muscidae]; Kurintjimyia Townsend, 1926 under Tachina Meigen, 1803, n. syn. [Tachinidae]; Labidigaster Macquart, 1844 under Labigastera Macquart, 1834, n. syn. [Tachinidae]; Mellanactia Guimarães, 1971 under Oxynops Townsend, 1912, n. syn. [Tachinidae]; Ochromia Townsend, 1935 under Bengalia Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Pachyrrhina Osten Sacken, 1881 under Nephrotoma Meigen, 1803, n. syn. [Tipulidae]; Procraspedothrix Townsend, 1932 under Phytomyptera Rondani, 1844, n. syn. [Tachinidae]; Pseudogymnosoma Townsend, 1918 under Neomyia Walker, 1859, n. syn. [Muscidae]; Pseudoservillia Townsend, 1916 under Tachina Meigen, 1803, n. syn. [Tachinidae]; Rhymosia Mik, 1886 under Rymosia Winnertz, 1863, n. syn. [Mycetophilidae]; Rhynchomyia Macquart, 1835 under Rhyncomya Robineau-Desvoidy, 1830, n. syn. [Rhiniidae]; Servillioides Townsend, 1926 under Tachina Meigen, 1803, n. syn. [Tachinidae]; Servilliopsis Townsend, 1916 under Tachina Meigen, 1803, n. syn. [Tachinidae]; Stephanostoma Cole, 1923 under Bercaea Robineau-Desvoidy, 1863, n. syn. [Sarcophagidae]; Stomatorhinia Townsend, 1935 under Stomorhina Rondani, 1861, n. syn. [Rhiniidae]; Toxorrhina Osten Sacken, 1869 under Toxorhina Loew, 1850, n. syn. [Limoniidae]; Trichoneura Townsend, 1935 under Stevenia Robineau-Desvoidy, 1830, n. syn. [Rhinophoridae]; Trichopticus Schnabl, 1889 under Thricops Rondani, 1856, n. syn. [Muscidae]; Tricyclopsis Townsend, 1916 under Paracalliphora Townsend, 1916, n. syn. [Calliphoridae].